Justice with algorithms and Artificial Intelligence, supporting procedural guarantees and rights or liquidating them? - Barona Vilar, Silvia (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2024)
The dataisation of life, of society, in the 21st century has become an indisputable reality, reaching also the algorithmisation of Justice. The challenges and risks are enormous and the outlook is complex. We are witnessing an ever-increasing “hybridisation” of Justice: machines and humans interact, algorithms assist legal operators, systems are created to complement the decisions of judges, prosecutors, lawyers, notaries, etc., although, increasingly, we are moving towards the progressive replacement of human beings in Justice by machines, by robots. The dilemma of the Justice is present. We must avoid imbalance, inequalities, the digital divide, the reduction of guarantees, the conversion of Justice into cold statistical-mathematical data, which perverts the human model of Justice; a model with shortcomings but which has been built on the basis of respect for rights and guarantees.